Crepidula argentina, (Gastropoda; Calyptraeidae) a new species from the littoral of Argentina - Simone, Luiz Ricardo L. (2000)
Crepidiila argentina, a new species of gastropod of the family Calyptraeidae, is described from the littoral of Mar del Plata, province of Buenos Aires, Argentina...